Pelatihan Akuntansi Perpajakan Mitra Industri Properti - Novi Nugrahanti; Indra Lukmana Putra; Muhammad Kholisul Imam; Atika Syuliswati; Aisyah Vanadia Rubianto; Peni Puspitasari (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
This community service activity focuses on strengthening the understanding and application of tax accounting in the property industry, essential for improving tax compliance and efficiency. The targets of this activity include industry partners in the property sector located in Surabaya and Batu, East Java, as well as students involved in developing their practical skills. This activity aims to strengthen the skills of industry partners in tax calculation and reporting and develop solutions that can be integrated into their tax accounting practices. The methods used include observation to identify challenges and needs of industry partners, theoretical and practical training on tax calculation, and evaluation of activity results through questionnaires. The evaluation results showed a significant increase in the knowledge and skills of industry partners related to tax accounting. The evaluation also identified the need to integrate tax planning into management and develop more efficient tax accounting applications.